Sturge–Weber syndrome – A case report - Shahid M. Shaikh; Mousumi Goswami; Sanjay Singh; Darrel Singh (Journal of Oral Biology and Craniofacial Research)
Sturge–Weber syndrome (SWS), also called as encephalotrigeminal angiomatosis is an uncommon congenital neurological disorder & frequent among the neurocutaneous syndromes specifically with vascular predominance. This disorder is characterized by facial capillary malformation & other neurological condition. The oral manifestations are gingival hemangiomatosis restricting to either side in upper and lower jaw, sometimes bilateral. We report a case of SWS with oral, ocular and neurological features.